CITRAAN DALAM NOVEL TANAH SURGA MERAH KARYA ARAFAT NUR - Saputro, Yudha Kretiyanto; Sutejo; Suprayitno, Edy (STKIP PGRI Ponorogo Press, 2021)
Literary works are essentially the writers’ embodiment of the realities of life around them. Tanah Surga Merah novel by Arafat Nur tells the story of the character Murad, who sets foot on the land of Aceh after his escape. There are a lot of stories that Murad experienced while in his homeland. The purpose of this research is to describe the image contained in the Tanah Surga Merah novel and its function. The method used in this research is descriptive qualitive method. Data collection techniques in this study using reading notes technique. The researcher found five types of images contained in the Tanah Surga Merah novel, as follows: visual images, hearing, touch, motion and smell. They functions as a means of descending character, setting, plot and theme in the novel. This research needs to be refined to get more detailed results. For further research can add image elements that come from other theories or combine several theories related to statistical research.